2003
DOI: 10.1111/1467-9701.00539
|View full text |Cite
|
Sign up to set email alerts
|

Capital Inflows and the Real Exchange Rate: A Comparative Study of Asia and Latin America

Abstract: The nexus of real exchange rate (RER) and capital inflows is examined through a comparative analysis of the experiences of emerging market economies in Asian and Latin America during the period 1985-2000. It is found that the degree of appreciation in RER associated with capital inflow is uniformly much higher in Latin American countries compared to their Asian counterparts, despite the fact that the latter experienced far greater foreign capital inflows relative to the size of the economy. The econometric evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
87
1
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(102 citation statements)
references
References 25 publications
10
87
1
4
Order By: Relevance
“…Exchange rate stability can help to explain FDI inflows on condition that the host country's economy is liberalized (Emmanue and Luther, 2014). Athukoraka and Rajapatirana (2003) observed that real exchange rates strengthened in response to the total capital flows whilst the same study further revealed that an increase in FDI inflow in particular led to the weakening of the real exchange rate in Asian and Latin American countries. In addition, the strengthening of the real exchange rate in response to increased capital inflows was more pronounced in Asian countries as compared to in Latin American countries, argued Athukoraka and Rajapatirana (2003).…”
Section: Review Of Related Literaturementioning
confidence: 79%
See 2 more Smart Citations
“…Exchange rate stability can help to explain FDI inflows on condition that the host country's economy is liberalized (Emmanue and Luther, 2014). Athukoraka and Rajapatirana (2003) observed that real exchange rates strengthened in response to the total capital flows whilst the same study further revealed that an increase in FDI inflow in particular led to the weakening of the real exchange rate in Asian and Latin American countries. In addition, the strengthening of the real exchange rate in response to increased capital inflows was more pronounced in Asian countries as compared to in Latin American countries, argued Athukoraka and Rajapatirana (2003).…”
Section: Review Of Related Literaturementioning
confidence: 79%
“…For countries whose trade openness was above 125%, the impact of exchange rate volatility was found to be negative whereas those countries characterized by less than 125%, the influence of exchange rate volatility on FDI were found to be positive (Furceri and Borelli (2008). Athukoraka and Rajapatirana (2003) showed that real exchange rates strengthened in response to the total capital flows whilst the same study further revealed that an increase in FDI inflow in particular led to the weakening of the real exchange rate in Asian and Latin American countries. The study by Athukoraka and Rajapatirana (2003) further revealed that the appreciation of the real exchange rate in response to increased capital inflows was more pronounced in Asian countries as compared to in Latin American countries, an indication that the impact can be region specific.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…A number of empirical studies (e.g., Ito 2000, Lipsey 2000, Athukorala and Rajapatirana 2003 argue that the appreciation of RER associated with net FDI inflows could be smaller than that associated with portfolio and bank lending flows. Compared to other flows, FDI has a general tendency to concentrate more on the tradable goods sector and export-oriented industry.…”
Section: Determinants Of Real Exchange Rate: Analytical Frameworkmentioning
confidence: 99%
“…The symptoms of Dutch Disease derived from foreign direct investment (FDI) inflows were initially analysed by (Athukorala and Rajapatirana, 2003) (Lartey, 2007), using dynamic panel data for a set of Sub-Saharan countries, shows that FDI is positively correlated with RER appreciation and, consequently, with losses of competitiveness in exports. Similar conclusions are obtained by (Javaid, 2011) for a group of Southeastern Asian economies.…”
Section: Other Initial Forms Of Dutch Diseasementioning
confidence: 99%